2010
DOI: 10.1111/j.1365-3059.2010.02284.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of seed‐tuber and soilborne inoculum in causing black dot disease of potato

Abstract: dSutton Bridge Experimental Unit, Sutton Bridge, Lincolnshire, PE12 9YD, UK Controlled-environment and field experiments were done to quantify the individual contribution of seed-tuber and soilborne inoculum of Colletotrichum coccodes in causing black dot disease of potato tubers. Seed-tuber and soilborne inocula of C. coccodes were quantified using an existing real-time PCR assay and related to subsequent incidence and severity of disease. In four field trials, a controlled-environment experiment and through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 19 publications
3
25
1
Order By: Relevance
“…Lees et al . () reported that in controlled environment experiments black dot severity was higher in the damp treatment compared to the treatment with restricted water (half that given to damp treatments). Olanya et al .…”
Section: Discussionmentioning
confidence: 95%
“…Lees et al . () reported that in controlled environment experiments black dot severity was higher in the damp treatment compared to the treatment with restricted water (half that given to damp treatments). Olanya et al .…”
Section: Discussionmentioning
confidence: 95%
“…Twenty‐seven soils sampled from potato fields in 2006 (as detailed by Lees et al. , 2010) were tested using the soil DNA extraction method of Brierley et al.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore the denser sampling strategy is most cost-effective with regard to the potential for a more reliable prediction. The sampling density of 25 cores/sampling points per ha is similar to sampling densities used for detection and quantification of other soil-borne pathogens, like Colletotrichum coccodes and Rhizoctonia solani in potatoes in the UK (Lees et al 2010;Peters et al 2011).…”
Section: Discussionmentioning
confidence: 98%